Facilitating multi-stakeholder dialogue to manage natural resource competition: A synthesis of lessons from Uganda, Zambia, and Cambodia - Ratner, Blake D.; Burnley, Clementine; Mugisha, Samuel; Madzudzo, Elias; Oeur, Il; Mam, Kosal; Rüttinger, Lukas; Chilufya, Loziwe Njobvu; Adriázola, Paola (Uopen Journals, 2017)
Rural development or natural resource management program planning and implementation frequently confront challenges of environmental resource competition and conflict, particularly where common pool resources are a major component of rural livelihoods. This paper reports on an approach to multistakeholder dialogue, supported by participatory action research, to address the roots of such competition and conflict. The approach, called "Collaborating for Resilience," includes principles and guidance on building a shared understanding of risks and opportunities, weighing alternative actions, developing action plans, and evaluating and learning from the outcomes. Working in partnership with government, community and civil society actors, the approach was developed and refined through applications in large lake systems in Uganda, Zambia, and Cambodia. This paper presents a synthesis of lessons addressing practitioners in government, nongovernmental development organizations, and international development agencies. These lessons include guidance on the context of multistakeholder dialogue processes, addressing gender equity, building stakeholder relationships and accountability across scales, and encouraging learning and innovation over time.